2012
DOI: 10.4081/ija.2012.e38
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting soil organic matter conservation in Mediterranean hillside winter cereals-legumes cropping systems

Abstract: Soil conservation is an important issue for farming and environmental protection in Mediterranean areas. Hillside farming systems, based on winter cereals and legumes, are common in these areas and are the target of several environmental policies. Soil organic matter (SOM) is widely used to assess the environmental performance of these cropping systems. Nevertheless, few studies have considered soil conservation practices in hillside systems in terms of implementing more effective agro-environmental policies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…2). Also local agriculture follows the main trend of Mediterranean agriculture: the number of farms decreased from 1990 to 2010 (-56%), especially for vegetables (-92%), while mean farm size slightly increased for all the farming systems (Marraccini et al 2012). This periurban area is relevant for our analysis not just because of its administrative borders and distance from the largest and most important city, but also because of its geographic borders, which have created a unique social identity compared to nearby areas.…”
Section: Methodsmentioning
confidence: 98%
“…2). Also local agriculture follows the main trend of Mediterranean agriculture: the number of farms decreased from 1990 to 2010 (-56%), especially for vegetables (-92%), while mean farm size slightly increased for all the farming systems (Marraccini et al 2012). This periurban area is relevant for our analysis not just because of its administrative borders and distance from the largest and most important city, but also because of its geographic borders, which have created a unique social identity compared to nearby areas.…”
Section: Methodsmentioning
confidence: 98%
“…The quantity of C input (t ha −1 yr −1 ) from cover crop residue required to maintain SOC steady-state levels (C maintain = C m ) was calculated for each soil functional group according to the organic matter balance that take into consideration the humified and mineralized fraction (Marraccini, Debolini, Di Bene, Rapey, & Bonari, 2012).…”
Section: Reference C Stocks and Change Factorsmentioning
confidence: 99%
“…A value of 60% was used for the stable C fraction, as previous studies in the same environment showed that this is the percentage of SOC which is mainly stored in the finest soil aggregate fraction (<25 μm) and therefore the most recalcitrant (Barbera et al, 2012;Novara et al, 2016). The humification coefficient of durum wheat straw was assumed to be 0.15 (Marraccini et al, 2012). The k constant, which is affected by air average temperature, clay and carbonate content, was calculated according to Boiffin et al (1986) and Bockstaller and Girardin (2003).…”
Section: Input Maintainmentioning
confidence: 99%